A validation study for the estimation of uniaxial compressive strength based on index tests - Kong, Fanmeng (2020)
Uniaxial compressive strength (UCS) is one of the crucial parameters controlling the strength of rock masses (Hu et al. 2012). A reliable and direct measurement of this parameter in the laboratory requires well-prepared samples and certified testing apparatus (Heidari et al. 2012). As an indirect method, index tests have been widely used to estimate the UCS of rock, especially in the field. The index tests can be performed using simple equipment such as portable point load testers and Schmidt hammers. Up to now, the relationship between UCS and the results of index tests has been widely discussed (Hoek 1977; Aggistalis et al. 1996; Fener et al. 2005; Karaman and Kesimal 2015). The validity of the index tests, however, remains poorly understood; results of the tests may vary due to lithological heterogeneity mainly arising from geological bedding and schistosity, grain size variation and micro-fractures. For example, point load test results may vary significantly (by a factor up to 2) when samples drilled with different orientations relative to bedding planes are used (Broch 1983). Broch (1983) pointed out that the most reliable strength index can be obtained when samples are drilled normal to bedding planes. In addition, when a tested rock surface contains coarse grains with sizes comparable to the plunger tip diameter, the readings of Schmidt hammers can vary significantly, depending on their strength relative to the dominant grain size of the tested rock (Aydin 2009). Situations become worse when micro-fractures exist (unseen by the naked eye). It is therefore questionable about the validity of the index tests in the estimation of UCS, because the variation of the index test results can be attributed to (1) lithological heterogeneity of the tested rock samples (as described above) and (2) the validity of the index tests themselves.